Maghreb´s Population: Current Situation and Dymanics - Abad, Gracia (UNISCI Discussion Papers, 2014)
The demographic situation of the Maghreb States seems to be in sharp contrast with that of the Northern Mediterranean States like Spain. They show a trend of population growth. The population is relatively young and there is no risk of ageing, at least until the second half of this century. All in all, it should be noticed that these States might be at the beginning of a demographic transition as some indicators, albeit slowly, seem to start changing. Besides, the Maghreb States would be experiencing a process of migration from rural to urban areas as a consequence of the lower quality of life in the rural areas. This might be feeding unemployment rates and pushing Maghreb population to migrate to foreign countries.
Keywords: Maghreb; population; growth; ageing; Algeria; Morocco; Tunisia.